1996
DOI: 10.1111/j.1558-5646.1996.tb03614.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Learning‐related Neuromodulation in Molluscan Mechanosensory Neurons

Abstract: In spite of significant advances in our understanding of mechanisms of learning and memory in a variety of organisms, little is known about how such mechanisms evolve. Even mechanisms of simple forms of learning, such as habituation and sensitization, have not been studied phylogenetically. Here we begin an evolutionary analysis of learning-related neuromodulation in species related to the well-studied opisthobranch gastropod, Aplysia californica. In Aplysia, increased spike duration and excitability in mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 39 publications
2
41
1
Order By: Relevance
“…Finally, the original motivation for executing these experiments was physiological research in our laboratory, which found significant phylogenetic variation in mechanisms of sensitization across 7 aplysiomorph species (Wright et al 1996, Erixon et al 1999, as well as behavioral experiments verifying correlated variation in behavioral phenotypes (Wright 1998, Erixon et al 1999, Marinesco et al 2003. Sensitization is a simple form of learning, which refers to the strengthening of defensive reflexes following a noxious stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the original motivation for executing these experiments was physiological research in our laboratory, which found significant phylogenetic variation in mechanisms of sensitization across 7 aplysiomorph species (Wright et al 1996, Erixon et al 1999, as well as behavioral experiments verifying correlated variation in behavioral phenotypes (Wright 1998, Erixon et al 1999, Marinesco et al 2003. Sensitization is a simple form of learning, which refers to the strengthening of defensive reflexes following a noxious stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Although chemical defenses have been well studied in Aplysia and its relatives (Carefoot 1987, Pennings 1994, Avila 1995, Nolen & Johnson 2001, Kicklighter et al 2005, Nusnbaum & Derby 2010, chemical defenses in Phyllaplysia and Dolabrifera have been scarcely studied (Ciavatta et al 1996). We chose these 3 species (Phyllaplysia and Dolabrifera are sister genera in the subfamily Dolabriferinae, and Aplysia is a more distant relative in the subfamily Aplysiinae; Klussmann-Kolb 2004) because we have previously discovered significant variation among them in a simple form of learning called sensitization (Wright et al 1996, Wright 1998, Erixon et al 1999, Marinesco et al 2003. Sensitization refers to a generalized increase in reflex response after a novel or noxious stimulus (Kandel 2004, Barco et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In Phyllaplysia taylori, the modulatory effects of noxious stimulation of sensory neurons although significant, are weaker than those observed in Aplysia. This is likely due to inhibition by unknown mechanisms, because serotonin release ) and the response of sensory neurons to serotonin (Wright et al 1996), are indistinguishable from that of Aplysia. At the behavioral level, Phyllaplysia shows only very limited sensitization (Erixon et al 1999).…”
mentioning
confidence: 99%
“…Both of these nonassociative manipulations cause neuromodulatory changes in sensory-neuron firing properties of Aplysia, but their effects on two related species are much weaker. Specifically, in Dolabrifera dolabrifera, no serotonin-induced changes are observed, and a cladistic analysis (Wright et al 1996) strongly suggests that this absence is due to a relatively recent evolutionary loss of response by sensory neurons to applied serotonin. Furthermore, stimulation of peripheral nerves has no effect on sensory neurons, and behavioral experiments (Wright 1998) confirm the complete lack of sensitization (short-or long-term) or dishabituation.…”
mentioning
confidence: 99%
See 1 more Smart Citation